Bullets to ballots collective de-radicalisation of armed movements (Edinburgh University Press, 2021)
Bullets to Ballots explores the different trajectories that the deradicalisation process can take - whether it occurs after a military victory, a military defeat, or a draw in an armed conflict between insurgent groups and incumbent authorities.